Assessing quality of online learning platforms for in-service teachers’ professional development: The development and application of an instrument - Zhang, Jing; Wang, Bing; Yang, Harrison Hao; Chen, Zengzhao; Gao, Wei; Liu, Zhi (Frontiers in Psychology, 2022)
An effective and standardized online learning assessment tool is an urgent requirement to help optimize online learning platforms for teachers and enhance teachers’ satisfaction with online training for their lifelong professional development and the sustainable development of online education. As online learning became the main mode of education during COVID-19, evaluating the quality of online learning platforms is imperative. Based on the information systems success (IS) theory and related studies, this study develops a set of original evaluation questionnaires for teachers from aspects of content quality, technical quality, and service quality. After reliability and validity tests and expert empowerment, we organized a set of weight-based quality measurement instruments per user experience, enabling the assessment of teachers’ professional development in an online learning platform (QM-TPDOP) equipped environment. Moreover, the evaluation tool QM-TPDOP was used to analyze the optimization of the National Teacher Training Platform amid the COVID-19 outbreak in China. The findings revealed that the optimization of the platform’s style, tool function, operating efficiency, and teaching methods could bring about significantly higher teachers’ satisfaction with online training. Furthermore, the research outcome provides guidelines for online teacher education in areas where normal face-to-face teaching and learning in schools have not started owing to COVID-19 and for teachers’ professional development online in future.